2018
DOI: 10.1128/jcm.00517-18
|View full text |Cite
|
Sign up to set email alerts
|

Core Genome Multilocus Sequence Typing and Single Nucleotide Polymorphism Analysis in the Epidemiology of Brucella melitensis Infections

Abstract: The use of whole-genome sequencing (WGS) using next-generation sequencing (NGS) technology has become a widely accepted method for microbiology laboratories in the application of molecular typing for outbreak tracing and genomic epidemiology. Several studies demonstrated the usefulness of WGS data analysis through single-nucleotide polymorphism (SNP) calling from a reference sequence analysis for Brucella melitensis, whereas gene-by-gene comparison through core-genome multilocus sequence typing (cgMLST) has no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 37 publications
3
79
0
Order By: Relevance
“…The number of SNPs encountered between the ten isolates ranged from zero to five, in the same range as the wgMLST variation and insufficient to decipher transmission of strains between patients (data not shown). Of note, a recent cgMLST study for Brucella melitensis revealed similar findings: epidemiological cutoff values for nonvariance were defined as Ͻ6 loci for wgMLST and Ͻ7 loci for wgSNP analyses, similar to what we document here for S. marcescens (19).…”
Section: Resultssupporting
confidence: 71%
“…The number of SNPs encountered between the ten isolates ranged from zero to five, in the same range as the wgMLST variation and insufficient to decipher transmission of strains between patients (data not shown). Of note, a recent cgMLST study for Brucella melitensis revealed similar findings: epidemiological cutoff values for nonvariance were defined as Ͻ6 loci for wgMLST and Ͻ7 loci for wgSNP analyses, similar to what we document here for S. marcescens (19).…”
Section: Resultssupporting
confidence: 71%
“…Phylogenetic analysis of Brucella melitensis loci [16], and the other runs on a pay-per-use platform (RIDOM SeqSphere) despite involving a wider core gene set of 2704 targets [17].…”
Section: Plos Onementioning
confidence: 99%
“…With the technological advances and decreased cost of whole genome sequencing, new methods of pathogen typing, including gene-by-gene comparison using core genome multilocus sequence typing (cgMLST), as well as single-nucleotide polymorphism (SNP) calling based on a reference sequence analysis, are considered to be a suitable and more informative replacement of the gold standard typing schemes [16]. Although the SNP-based analysis may constitute a better option for phylogenetic analyses of conserved genomes (because this approach covers the entire genome, including the intergenic regions) [17], very recently, efforts to develop cgMLST schemes for Brucella have been done [16,17]. One of these schemes involves 2704 genes and is based on a pay-per-use platform [17], whereas the other involves a strikingly low number of genes (n = 164) for differentiating purposes [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the growing amount of comparative studies (de Been et al, 2015;Li et al, 2017;Ghanem and El-Gazzar, 2018;Halbedel et al, 2018;Janowicz et al, 2018;Meehan et al, 2018), it is currently often unknown which approach is the most suitable for a given organism and in a given epidemiological situation, and the dissimilarities in the output obtained using alternative approaches have been poorly characterized. This is a second problem that slows down the adoption of WGS in routine, i.e., the absence of an established methodology for the evaluation and comparison of WGS data analysis schemes.…”
Section: Introductionmentioning
confidence: 99%